Возрастные изменения подвижности позвоночника школьников: лонгитюдный аспект - Акопян, Е. С.
Longitudinal observation of the dynamics of C inal mobility of 7-17 years old st udents are organized. The results of many years research it possible to identify a number of patterns that characterize the features of the functioning of the C ine, as well as to identify critical periods in its ontogeny.
Keywords: Дети с нарушением опорно-двигательного аппарата